Improved Physico-Mechanical Properties and Microstructure of Modified Kenaf Fiber Reinforced Composites - Eka Marya Mistar; Muhammad Muhammad (UNIVERSITAS SEBELAS MARET (UNS), 2025)
This study examined the properties of chemically modified kenaf fiber using propionic anhydride as reinforcement in vinyl ester composites. The composites reinforced by unmodified and modified kenaf fibers were fabricated using 10, 20, 30, 40, and 50% (w/w) via a hand lay-up technique. This study’s characterization included water absorption, thickness swelling, tensile and flexural strengths, and morphological analyses. The optimum physical, mechanical, and morphological properties were observed from the composite with 40% modified kenaf fiber. The optimized composite showed a considerable enhancement in the water absorption, tensile strength, and flexural strength of 1.82%, 54.90 MPa, and 55.85 MPa, respectively. These findings were supported by the fracture morphology after the mechanical test, exhibiting an enhanced interfacial modified kenaf fiber-matrix bonding. The improved characteristics of the composite were ascribed to the impact of the modification process within the fiber-matrix structures. Modified kenaf fiber via propionylation can be applied as a reinforcement material in the vinyl ester matrix.